(Re)creating Rituals: Considerations on Art, Judaism, and Feminism - Gueller, Viviane (Farol, 2025)
This article investigates poetic and political aspects related to the theme of motherhood, situations that arise when inventing oneself as a mother and caregiver through the creation of an artistic work. The text addresses the conception and development of a novel artistic intervention reinventing the minyan; a Jewish ritual marked by male protagonism, referring to the minimum quorum of ten adult Jewish men required for a public prayer. The proposal is to compose a minyan exclusively for women, reinventing and updating traditions, and thereby seeking to find meanings within them linked to contemporary issues. To anchor these approaches, connections are made with Jewish feminism in the work of visual artist Mierle Ukeles and German and Austrian Jewish salonnières, as well as notions proposed by authors Natalie Wichmann and Charlotte Burns.